Fabrication and properties of Carbon nanotube (CNT)-reinforced aluminium composites - Mohamed, Ahmed Sayed Salim (AUC Knowledge Fountain, 2010)
Nanostructured materials have attracted many researchers due to their outstanding mechanical and physical properties. One example is Carbon Nanotube (CNT) reinforced composites. Although most researchers have focused on using CNTs to reinforce polymeric and ceramic matrices, CNT-reinforced metallic composites are quickly emerging as attractive materials combining light weight with superior strength and stiffness. Potential applications include automotive and aerospace industries. In this research work, powder metallurgy techniques were employed to produce a nano composite with unique mechanical properties. 99.7% purity Aluminium (Al) powder was used along with two different types of multiwall carbon nanotubes (MWCNTs) having different aspect ratios to produce Al-CNT composites. In the first phase of the work, Al-CNT composite powders were produced by mechanical milling at low milling speed (200 rpm) for 3 and 6 hours using one type of CNT (140nm diameter) whereas in the second phase pure Al and up to 5 wt% of two types of CNT (40nm and 140nm diameters) were milled at the highest available speed (400 rpm) for 30 minutes. The composite powders were processed into bulk material by compaction, and hot extrusion using a cylindrical compaction and extrusion die with extrusion ratio 4:1. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-Ray diffraction (XRD) were used to evaluate CNT dispersion, powder morphology, CNT damage, phase analysis and crystal size determination. Tensile testing, microhardness and nanoindentation were used to characterize the mechanical properties. For the powders milled at 200 rpm for 6 hrs, the samples demonstrated high notch sensitivity and consistently fractured outside the gauge length during tensile testing. This necessitated annealing at 500 â ¦C for 10 h prior to testing to enhance ductility. Reduction in milling time from 6 to 3 hrs was also investigated in order to reduce the work hardening of the aluminium matrix and to accentuate the reinforcing effect of the CNT. The composite samples that were milled for 3 hrs and annealed at 500C resulted in the best enhancement in tensile strength (21%) compared with pure Al with the same process history. Also, it was proven by XRD that a nanostructure is present in all samples; that structure was retained after annealing at high temperatures. The tensile testing fracture surfaces showed uniform dispersion and alignment of the CNTs in the Al matrix. Regarding the powders milled at 400 rpm for 30 min using two types of CNT, it was found that the aspect ratio of CNT had an effect on dispersion, carbide formation, and CNT damage. As a result, the mechanical properties of the composite were significantly affected. Despite the theoretically expected advantage of reinforcements with higher aspect ratios, it was found that the difficulty in dispersing higher aspect ratio CNTs generally led to a decrease, rather than an increase, in tensile properties and hardness. Concerning the effect of CNT content, enhancements of 96% in tensile strength, 33% in Young's modulus, and 119% in hardness were observed for the sample containing 2 wt% of the large diameter CNT. It is thus concluded that high energy ball milling and powder metallurgy techniques are attractive manufacturing techniques for the fabrication of CNT-reinforced aluminium with enhanced mechanical properties. However, careful selection of the type and amount of CNT, the milling conditions and the processing parameters should be exercised.